The effect of bi-cropping wheat (Triticum aestivum) and beans (Vicia faba) on forage yield and weed competition. Issue 1 (2nd January 2020) - Cannon, Nicola D.; Kamalongo, Donwell Ma; Conway, John S.
ABSTRACT: Field experiments were conducted from April 2015 to September 2016 at the Royal Agricultural University, UK to explore the impact of drilling pattern and species mixtures on weed growth and forage yield. The bi-crops of spring field bean ( Vicia faba ) cv. Maris Bead and Fuego with spring wheat ( Triticum aestivum ) cv. Paragon were evaluated at four drilling patterns in a randomized complete block design with four replicates and compared against their respective sole crops. Weed DM was 59% higher in the sole cropping systems than the bi-cropping systems. The sole cropping systems outperformed the bi-cropping systems for wheat (in 2016 only) and for bean forage DM yield. However, the bi-cropping systems produced higher total forage DM yields than sole cropping systems. Weed DM was higher in broadcast than in alternate rows systems. Bean forage DM was 74% higher in treatments with alternate rows than in the broadcast treatment. Wheat forage DM was not affected by the drilling patterns. Maris Bead had higher forage DM than Fuego (in 2016 only). It was concluded that bi-cropping can increase land productivity per unit area over sole cropping, whilst improving forage DM yield and providing low cost integrated weed management. Alternate row drilling can improve bi-cropping productivity over the broadcast practice. Abbreviations: LER - Land Equivalent Ratio